Hak atas Pekerjaan bagi Penyandang Disabilitas di Sektor Publik: Antara Model Disabilitas Sosial dan Medis - Muhammad Dahlan; Syahriza Alkohir Anggoro (Fakultas Hukum Universitas Jambi, 2021)
The opportunity to fulfill the rights to work for persons with disabilities has been increasing since the ratification of Convention on the Rights of Persons with Disabilities (CRPD). Indonesia has adopted a “quota scheme” through the Law Number 8 of 2016 on Persons with Disabilities where government institution has set a minimum quantity of two percent as the number of workers for persons with disabilities as affirmative action targeted at promoting human rights. This article examines the progress of the legal framework for persons with disabilities by using a case study in civil cervants in the public sector. We argue that despite Indonesia’s disability legal regime has pushed the social model of disabilities that promotes human rights-based approach, its implementation is still based on the medical model of disability, in which it sees persons with disabilities on physical condition, and thus, they are assumed to be able to work in a certain field determined by the government. This article argues that affirmative policy does not provide equal opportunities to persons with disabilities as the special formation and medical requirements prevent them from applying for occupations that match their interests and educational background. The use of the medical model of disability in providing employment opportunities in the public sector prevents the level of participation and the formation of an inclusive workplace environment. Abstrak Peluang untuk memenuhi hak atas pekerjaan bagi para penyandang disabilitas terus meningkat sejak ratifikasi Convention on the Rights of Persons with Disabilities (CRPD). Indonesia mengadopsi “skema kuota” melalui UU Nomor 8 Tahun 2016 tentang Penyandang Disabilitas di mana institusi negara menetapkan minimal dua persen jumlah formasi pekerja bagi para penyandang disabilitas sebagai tindakan afirmatif yang ditargetkan untuk mempromosikan hak asasi manusia. Artikel ini memeriksa sejauh mana kerangka kerja hukum disabilitas di Indonesia memfasilitasi pemenuhan hak atas pekerjaan bagi penyandang disabilitas dengan menggunakan contoh kasus pada penyelenggaraan ketenagakerjaan di sektor publik. Kami berpendapat bahwa meskipun rezim hukum disabilitas di Indonesia menekankan model sosial disabilitas yang mempromosikan pendekatan berbasis hak asasi manusia, implementasinya masih didasarkan pada model medis disabilitas yang memandang penyandang disabilitas berdasarkan kondisi fisik dan karenanya diasumsikan hanya dapat masuk pada bidang pekerjaan yang telah ditentukan oleh negara. Artikel ini berpendapat bahwa kebijakan afirmatif tidak memberikan peluang yang setara bagi penyandang disabilitas karena formasi khusus dan persyaratan medis menghambat mereka untuk melamar pada bidang pekerjaan yang sesuai dengan minat dan latar belakang pendidikannya. Penggunaan model medis disabilitas dalam penyelenggaraan kesempatan kerja di sektor publik pada gilirannya menghambat tingkat partisipasi dan pembentukan lingkungan kerja yang inklusif.